Wafer-level fabrication of alkali vapor cells using in-situ atomic deposition. (14th December 2020) - Bopp, D G; Maurice, V M; Kitching, J E
Abstract: We demonstrate a new technique for filling mm-scale microfabricated silicon and glass cavities with alkali vapors at the wafer-scale. A single etched silicon wafer contains an array of cavities containing alkali precursor materials offset laterally from the cell array. The wafer is heated to create an array of alkali droplets on an upper glass wafer, which is then translated laterally under vacuum and bonded to create the cells. This technique can be implemented in a commercially available bonding tool, allows the fabrication of cells with arbitrary buffer gas contents and pressures and can potentially produce cells with dimensions below 100 µ m.